Introduction - Fineman, Martha Albertson (Columbia Journal of Gender and Law, 1992)
All of the papers included in this issue of the Columbia Journal of Gender and Law were presented at the first feminist issues workshop sponsored by the Feminism and Legal Theory Project at Columbia Law School. This workshop, entitled “Reproductive Issues in a Post-Roe World,” was organized in response to the changing political shape of the United States Supreme Court which made it apparent that there were some urgent questions to be considered. Over the space of two days, twelve presentations were made on diverse issues related to reproduction. As the papers in this issue indicate, the workshop was intended to take in a broad range of reproductive issues, for example, exploring how the changing world of reproductive technology affects women’s rights, as well as considering the regulation of midwifery.